Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40623-017-0775-3
|View full text |Cite
|
Sign up to set email alerts
|

Mean winds at the cloud top of Venus obtained from two-wavelength UV imaging by Akatsuki

Abstract: Venus is covered with thick clouds. Ultraviolet (UV) images at 0.3-0.4 microns show detailed cloud features at the cloud-top level at about 70 km, which are created by an unknown UV-absorbing substance. Images acquired in this wavelength range have traditionally been used to measure winds at the cloud top. In this study, we report low-latitude winds obtained from the images taken by the UV imager, UVI, onboard the Akatsuki orbiter from December 2015 to March 2017. UVI provides images with two filters centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 49 publications
(85 reference statements)
18
99
1
Order By: Relevance
“…The scale height is calculated to be H ~ 5.1 km. The zonal wind speed at the cloud top is assumed to be 100 m/s (e.g., Horinouchi et al, ), meaning that the intrinsic phase velocity is also 100 m/s in the opposite direction. From these parameters and the observed horizontal wavelength of ~510 km (section ), the wave period is 1.4 hr, corresponding to ω ~ 0.0012 s ‐1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale height is calculated to be H ~ 5.1 km. The zonal wind speed at the cloud top is assumed to be 100 m/s (e.g., Horinouchi et al, ), meaning that the intrinsic phase velocity is also 100 m/s in the opposite direction. From these parameters and the observed horizontal wavelength of ~510 km (section ), the wave period is 1.4 hr, corresponding to ω ~ 0.0012 s ‐1 .…”
Section: Resultsmentioning
confidence: 99%
“…Oscillations of the vertical wind that are attributed to topographic gravity waves have been observed by the VEGA balloons over Aphrodite Terra, which has a top altitude of 3–4 km (Blamont et al, ). Recently, Bertaux et al () suggested, based on cloud tracking using cloud images taken by the Venus Monitoring Camera onboard Venus Express, that the zonal wind speed decreases above Aphrodite Terra, probably due to momentum deposition by topographic gravity waves, although the result of cloud tracking using Akatsuki UVI data does not support this result (Horinouchi et al, ). A large number of small structures that are considered to be manifestations of topographic gravity waves were also found in the thermal maps of the cloud top on the nightside by the Visible and InfraRed Thermal Imaging Spectrometer onboard Venus Express (Peralta et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whole components showed almost hemispherical symmetry, but the amplitude of the semidiurnal tide in the northern hemisphere was slightly stronger than that in the southern hemisphere. Recently, an asymmetric structure was reported in zonal winds at the cloud top (Horinouchi et al, ). There could be a mechanism that induces the asymmetric condition in the Venusian atmosphere whose impact is worth investigating with a numerical approach.…”
Section: Global Structure Of Thermal Tidesmentioning
confidence: 99%
“…At the upper and middle clouds of Venus, the zonal superrotation exhibits the largest speeds and vertical shear (Sánchez‐Lavega et al, ) and is also where most of the solar energy is deposited (Titov et al, ). The upper clouds' top at ∼70 km (Ignatiev et al, ) can be observed with ultraviolet (UV) and violet wavelengths (∼360–480 nm), with their morphology and dynamics been extensively studied for decades (Belton et al, ; Horinouchi et al, ; Khatuntsev et al, ; Limaye et al, ; Rossow et al, , ; Titov et al, ), thanks to the strong contrasts caused by an unknown absorber (Lee et al, ; Pérez‐Hoyos et al, ).…”
Section: Introductionmentioning
confidence: 99%